Pengembangan Modul Lab Mandiri Roket Air Untuk Meningkatkan Pemahaman Konsep Dan Motivasi Belajar Siswa Pada Materi Hukum III Newton Di SMA Negeri 4 Langsa - Nurhaliza; Muhammad Yakob; Rizky Nafaida (Program Studi Pendidikan Fisika FKIP Universitas Samudra, 2019)
This research aims to increase the motivation of learning students and to find out how much improved the concept of understanding on the development of a water rocket independent lab module in newton’s legal material at SMA Negeri 4 Langsa. The study uses two stage method, the first phase using a R&D method with the 4-D development model and the second stage is an experimental research method with form one group pretest-postest design. The population on the study is class X MIPA SMA Negeri 4 Langsaconsisting of classes with samples taken in a random class X MIPA 1. The results of the study were a high motivation for the students after learning to use a water rocket independent lab module as much 85 % and there is an increase in understanding the conceptof development of a water rocket independent lab module on newton’s legal material III at SMA Negeri 4 Langsa. The sugestion for this research needs to be improved from this research to be improvet from the module readability level in support of students understanding of the material and students need more guidance from the teacher during the learning process. Keywords: Module, understanding concept and learning motivation for student